2014
DOI: 10.1186/s12933-014-0125-8
|View full text |Cite
|
Sign up to set email alerts
|

Does glycemic control reverse dispersion of ventricular repolarization in type 2 diabetes?

Abstract: BackgroundAbnormal ventricular repolarization is a predictor of cardiovascular mortality. In this study, we tested the hypothesis that glycemic control reverses abnormal ventricular repolarization in patients with type 2 diabetes.MethodsWe analyzed longitudinal changes in repolarization indices of electrocardiograms in retrospectively enrolled 44 patients with type 2 diabetes and 44 age-matched healthy subjects.ResultsIn the diabetic group, BMI was greater, levels of HbA1c (10.0 ± 1.6 vs. 5.6 ± 0.3%) and trigl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 45 publications
(56 reference statements)
2
26
1
Order By: Relevance
“…Recent studies have shown that ventricular repolarization is related with age, blood pressure values , and diabetes mellitus (32,17). In our study, the mean age of the blood pressure values were not different among peritoneal dialysis, hemodialysis, and healthy control groups.…”
Section: Türk Nefroloji Diyaliz Ve Transplantasyon Dergisi Turkish Necontrasting
confidence: 41%
See 2 more Smart Citations
“…Recent studies have shown that ventricular repolarization is related with age, blood pressure values , and diabetes mellitus (32,17). In our study, the mean age of the blood pressure values were not different among peritoneal dialysis, hemodialysis, and healthy control groups.…”
Section: Türk Nefroloji Diyaliz Ve Transplantasyon Dergisi Turkish Necontrasting
confidence: 41%
“…It was shown that Tp-e/QT was higher in patients with diabetes mellitus compared to the healthy control group (17). In our study group, there were 27 hemodialysis patients with diabetes mellitus and 36 peritoneal dialysis patients with diabetes mellitus.…”
Section: Türk Nefroloji Diyaliz Ve Transplantasyon Dergisi Turkish Nementioning
confidence: 52%
See 1 more Smart Citation
“…Moreover, increased dispersion of ventricular repolarization occurs in diabetic patients5, 6, 7, 8, 10 with an important implication on propensity to develop electrical disturbances 4, 13, 15, 16. To test the possibility that prolonged electrical recovery with hyperglycemia was associated with increased repolarization variability and rhythm disturbances, the degree of temporal dispersion of myocardial repolarization and susceptibility to develop arrhythmias were quantified.…”
Section: Resultsmentioning
confidence: 99%
“…Prolongation of the QT interval and increased dispersion of repolarization have been observed in the diabetic population,4, 5, 6, 7, 8, 9, 10 and these variables, together with intervening comorbidities,11 represent critical substrates for the occurrence of electrical disturbances 4, 12, 13, 14, 15, 16, 17. But whether alterations at the cellular level contribute to protracted electrical recovery and repolarization variability with diabetes remain to be determined.…”
Section: Introductionmentioning
confidence: 99%